2016
DOI: 10.13189/ujer.2016.040924
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Self-efficacy Beliefs in Teaching Science and Attitudes towards Teaching Profession of the Candidate Teachers

Abstract: The aim of this study is to investigate the attitudes of the primary school teacher candidates towards teaching profession and self-efficacy beliefs in teaching science. The research was conducted with a survey model. The sample of the study consisted of 182 teacher candidates who were studying at the 2015-2016 spring term from Kastamonu University, at Faculty of Education in Elementary Teacher Training program at the first and fourth years of university level. Scale of Self-Efficacy Beliefs towards Science Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A general self-efficacy score of 3.08 reflects this inexperience. These results are supported by earlier studies that reported first-level PSTs having lower self-efficacy than the more experienced fourth-level PSTs (Aslan, Tas, & Ogul, 2016;Uyanik, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A general self-efficacy score of 3.08 reflects this inexperience. These results are supported by earlier studies that reported first-level PSTs having lower self-efficacy than the more experienced fourth-level PSTs (Aslan, Tas, & Ogul, 2016;Uyanik, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Not being sure about whether these tasks will be difficult speaks to their immaturity as educators and their perceived skill sets. The more experienced the science teacher, the higher their self-efficacy (Aslan et al, 2014;Uyanik, 2016). Feeling inadequate in improving student motivation and performance (item 7) would lower self-efficacy because these two factors are powerful motivators for teacher behaviour and efficacy (Tschannen-Moran et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in the focus of education worldwide has also affected the role of teachers and students in the 21st century (Uyanık, 2016). Teachers are expected to share knowledge with students and to guide them to construct new knowledge as well as students are expected to become effective problem solvers in daily lives using mathematical and scientific knowledge and language (Colwell & Enderson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This encouragement leads to better self-regulation and better study habits (Bruce, Esmonde, Ross, Dookie, & Beatty, 2010). The higher efficacy of a mathematics or science teacher accepts and values students' suggestions, ideas, and judgements (Liu & Zhou, 2007), and as a result, students' achievement, motivation, performance, and self-efficacy beliefs related to science and mathematics increase (Aydin & Woolfolk Hoy, 2005;Çaycı, 2011;Chang, 2015;Işıksal-Bostan, 2016;Liu & Zhou, 2007;Tschannen-Moran & Hoy, 2001;Uyanık, 2016;Zamir, Arshad, & Nazir, 2017). Students with a high level of efficacy determine higher goals, work harder, and become more successful in science and mathematics than others with low selfefficacy (Chang, 2015;Pajares, 1992).…”
Section: Introductionmentioning
confidence: 99%